Cathodic stripping voltammetric determination of chromium in coastal waters on cubic Nano-titanium carbide loaded gold nanoparticles modified electrode - Han, Haitao; Pan, Dawei; Liu, Dongyan; Hu, Xueping; Lin, Mingyue; Li, Fei (Frontiers in Marine Science, 2015)
The novel cubical nano-titanium carbide loaded gold nanoparticles modified electrode for selective and sensitive detection of trace chromium (Cr) in coastal water was established based on a simple approach. Nano-titanium carbide is used as the typical cubical nanomaterial with wonderful catalytic activity towards the reduction of Cr(VI). Gold nanoparticles with excellent physical and chemical properties can facilitate electron transfer and enhance the catalytic activity of the modified electrode. Taking advantage of the synergistic effects of nano-titanium carbide and gold nanoparticles, the excellent cathodic signal responses for the stripping determination of Cr(VI) can be obtained. The detection limit of this method is calculated as 2.08 μg L-1 with the linear calibration curve ranged from 5.2 to 1040 μg L-1. This analytical method can be used to detect Cr(VI) effectively without using any complexing agent. The fabricated electrode was successfully applied for the detection of chromium in coastal waters collected from the estuary giving Cr concentrations between 12.48 and 22.88 μg L-1 with the recovery between 96% and 105%.